Analisis Sikap Pustakawan dalam Berinteraksi dengan Pemustaka Perpustakaan Sekolah Perguruan Islam Al-Ulum Terpadu Medan - Muhammad Farhan Maulana; Nurhayani Nurhayani (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
Attitude is an individual's response to an object, whether positive or negative, influenced by personal judgment of the object. Attitude can be seen as an individual's way of responding to or reacting to something. The librarian's attitude is one of the important factors in the success of a library. A librarian with a good attitude will be able to provide better service to library users and help improve the quality of the library's collection. This study aims to identify the attitudes of librarians in interacting with the users of the Library of Islamic Integrated Teacher Training School Al-Ulum Medan. The method used in this study is qualitative descriptive with data collection techniques through observation and interviews. There are 3 sources used in this study, all of whom are users of the Library of Islamic Integrated Teacher Training School Al-Ulum. The results of this study indicate that the librarians of the Library of Islamic Integrated Teacher Training School Al-Ulum have a friendly, reliable, and attentive attitude in interacting with library users.